Similarity Analysis of Physical Properties of Red Soils Formed from Quaternary and Tertiary Volcanic Parent Materials - Kusuma, Eka Widiawati Wijaya (Jurnal Biologi Tropis, 2025)
Indonesia hosts numerous active and inactive volcanoes that have produced a wide range of volcanic rocks, giving rise to diverse soil types, including red soils that are predominant in humid tropical regions. This study aimed to investigate the physical characteristics of two red soil pedons developed from Quaternary and Tertiary volcanic parent materials. Soil sampling was conducted at the Quaternary volcanic red soil pedon located in Tugu Village, Jumantono Sub-district, Karanganyar Regency, Central Java, and the Tertiary volcanic red soil pedon located in Nglanggeran Village, Patuk Sub-district, Gunungkidul Regency, Yogyakarta Special Region. Soil profile selection was conducted purposively based on morphological uniformity and representativeness. The analyzed soil physical properties included soil color, ten particle-size fractions, particle density, bulk density, and porosity. The highest degree of soil redness was observed in the Tertiary volcanic red soil pedon at Nglanggeran. This pedon comprises five horisons that mostly exhibit very low or uncertain degrees of similarity. In contrast, the Quaternary volcanic red soil pedon at Tugu consists of several horisons with comparable physical characteristics. Overall, the comparison between the Tertiary and Quaternary red soil pedons indicates substantial similarity, suggesting that the physical properties of mineral soils developed from volcanic materials are generally comparable despite differences in parent material age.